Integration of Humanistic Learning Theory in Islamic Education: A Psychopedagogical Study of Contemporary Educational Challenges - Mardhatillah, Mardhatillah; Batubara, Juliana; Deliani, Nurfarida (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to describe humanistic learning theory and examine its relevance within the context of Islamic education. Humanistic theory emphasizes holistic human development through meaningful learning experiences, freedom, self-actualization, and respect for learners’ dignity. This study employs a literature review method by analyzing the theories of Abraham Maslow and Carl Rogers, as well as scholarly works on Islamic education. The findings indicate that humanistic theory is aligned with the concept of Islamic education, which views human beings as endowed with fitrah (innate potential) and responsible for the development of their personal capacities. Humanistic learning is also found to be relevant in addressing contemporary educational issues, such as discrimination against students with special needs and excessive academic pressure that hinders learners’ psychological development. The integration of humanistic theory with Islamic values provides a conceptual foundation for fostering inclusive, empathetic, and humanizing educational practices.